Sitagliptin's effects on bone tissue and osseointegration in diabetic rats - Bautista, Cristhian Reynaldo Gomez [UNESP]; Santos, Ingrid Valadares dos [UNESP]; Moraes, Renata Mendonça [UNESP]; Chiba, Fernando Yamamoto [UNESP]; Sumida, Doris Hissako [UNESP]; de Moraes, Michele Bianchi [UNESP]; de Vasconcellos, Luana Marotta Reis [UNESP]; Anbinder, Ana Lia [UNESP] (Elsevier, 2019)
Objective: To investigate the effects of sitagliptin, a dipeptidyl peptidase 4 inhibitor used to treat type II diabetes, on bone tissue and on implant osseointegration in diabetic rats. Design: Thirty-two male rats were divided into four groups: 1) Diabetic animals (GD); 2) Diabetic animals that received sitagliptin (GDS); 3) Normoglycemic animals (GN); and 4) Normoglycemic animals that received sitagliptin (GNS). All animals received titanium implants in the right tibia. Sitagliptin or water were administered for 4 weeks. Glycemia, HOMA-IR, insulinemia, microtomographic parameters of the left tibia and implant bone area fraction occupancy (BAFO) of the right tibia were evaluated. Results: The model used to induce diabetes led to hyperglycemia. However, HOMA-IR results showed no insulin resistance, and insulinemia was lower in diabetic animals, demonstrating the development of type I diabetes. Sitagliptin administration did not influence glycemic control. The diabetic animals showed a lower BAFO and bone volume fraction, as well as a lower trabecular number and thickness, revealing the deleterious effect of diabetes on bone metabolism and osseointegration. Conclusion: In this model, sitagliptin administration did not reverse the negative effects of type I diabetes on bone, suggesting that sitagliptin has no direct action on bone tissue and has no protective bone action in decompensated diabetic animals.
Keywords: Dipeptidyl peptidase 4; Implants; Incretins